Collagen-Induced Platelet Aggregation as Studied by Electronic Particle Size Analysis - McLean, Margaret R; Hause, Lawrence L (Thrombosis and Haemostasis, 1981)
The collagen-induced response of free platelets during aggregation was measured with an electronic particle size analyzer. Aggregation was induced in platelet-rich plasma by 0.05 mg/mL collagen. The reaction was followed turbidimetrically and samples for electronic particle size analysis were obtained during aggregation.Free platelet number decreased rapidly after the addition of collagen. This decrease preceded detectable changes in transmittance and a significant reduction in free platelet number was measured during the classical lag phase. In addition, the size distribution of free platelets at variotrs times after the addition of collagen was not significantly altered indicating that large platelets are not preferentially involved in collagen-induced aggregation.
Keywords: Platelet aggregation; Collagen; Electronic particle Size analysis